Digital Zakat: An Analysis of Twitter Sentiment - Annisa Kartika Ocktavia; Assyifa Nur Aziza; Ihsanul Ikhwan (SMART Insight, 2023)
This research was conducted to examine the perception of digital zakat in the scope of Islamic economics from the point of view of sentiment research on Twitter social media users in responding to the development of digital zakat. The method used in this research is a qualitative approach with descriptive statistics from literature studies in the form of 1237 Twitter tweets. Python library software called VADER (Valence Aware Dictionary and Sentiment Reasoner) is used to classify tweets. The sentiment analysis results tended to perceive positive sentiment at 51.7%, neutral sentiment at 28.6% and negative sentiment at 19.7%. The variety of sentiment analysis results reflects the diversity of opinions regarding the progress of digital zakat. The benefit of this study is to contribute literature and considerations in relation to the development of digital zakat as well as identifying shortcomings and threats, such as negative perceptions towards the use of digital zakat. In addition, the objectives of this study also include understanding the positive views, advantages, potentials, and benefits of digital zakat. This research is the first comprehensive research that discusses sentiment analysis on the theme of digital zakat with Twitter tweet data. Suggestions for further research and recommendations are included.